Self-Paced Moodle Learning Advances Teachers Digital Competence Levels: Pembelajaran Mandiri Moodle Meningkatkan Tingkat Kompetensi Digital Guru - Rajab, Hafizh Fajar; Jubaedah, Edah; T. Gedeona, Hendrikus; Pradesa, Hafid Aditya Pradesa (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Digital competence has become a fundamental requirement for effective pedagogy in technology-integrated education systems. Specific Background: At SMAN 1 Nagreg, teachers’ use of digital tools remained limited, with most operating at the Newcomer and Explorer levels of the DigCompEdu framework and relying on conventional professional development approaches. Knowledge Gap: Empirical action research on self-paced e-learning models for secondary school teachers in resource-constrained settings remains limited, particularly regarding structured and iterative interventions. Aims: This study evaluates a Moodle-based self-paced e-learning program designed using the ADDIE framework within Classroom Action Research to improve teachers’ digital competencies across six DigCompEdu domains. Results: Findings indicate a transition from A1/A2 levels to the Integrator (B1) level, with notable progress in legal digital resource curation and interactive digital assessment practices. Teachers reported a 79.05% positive response rate, emphasizing flexibility as a key advantage, while time management remained a primary challenge. Novelty: The study demonstrates the integration of CAR and ADDIE within a self-paced Moodle environment as a structured intervention model for teacher professional development. Implications: Institutional support, including formal policy integration and protected learning time, is essential to sustain competency development and ensure broader adoption of self-paced digital training. Highlights• Transition from beginner to integrator competency stages across all DigCompEdu domains• Strong progression in ethical resource selection and data-driven evaluation practices• Flexible access model widely appreciated despite workload-related participation barriers KeywordsDigital Competency; DigCompEdu Framework; Moodle Learning Platform; Self-Paced Learning; Teacher Professional Development